Thursday
March 23, 2017

Post a New Question

Posted by on Tuesday, March 5, 2013 at 10:00pm.

(2c-d)/(c^2d)+(c+d)/(cd^2)

  • Rational expressions - , Tuesday, March 5, 2013 at 11:04pm

    LCD = c^2 d^2

    (2c-d)/(c^2d)+(c+d)/(cd^2)
    = ( d(2c-d) + c(c+d))/(c^2d^2)
    = (2cd - d^2 + c^2 + cd)/(c^2d^2)
    = (3cd - d^2 + c^2)/(c^2d^2)

    You did not say what you want done with it.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question